Effect of tide to storm surge in Do Son coastal zone, Hai Phong - Nguyen, Thanh Co; Dinh, Van Manh; Nguyen, Van Moi (Vietnam Journal of Marine Science and Technology, 2022)
The magnitude of storm surge depends on many factors: The intensity, direction, and speed of the storm, coastal topography, tidal height, etc. This paper presents the study results of the influence of tide on storm surge in Do Son coatal zone, Hai Phong City, based on the calculating results of storm surge in cases tidal and non-tidal storms landed into this coastal area from 1951 to 2020. The numerical model is used to calculate storm surge in this study is the TSIM11 model. This model can calculate wave, tide and storm surge and it was constructed by the Institute of Mechanics, Vietnam Academy of Science and Technology. The numerical model has been calibrated and validated using measurement data from stations in the study area.